2005
DOI: 10.1074/jbc.m502242200
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β Differentially Regulates β2 Adrenoreceptor and Prostaglandin E2-mediated cAMP Accumulation and Chloride Efflux from Calu-3 Bronchial Epithelial Cells

Abstract: Here we tested the effect of interleukin-1␤, a proinflammatory cytokine, on cAMP accumulation and chloride efflux in Calu-3 airway epithelial cells in response to ligands binding to adenylyl cyclase-coupled receptors such as the ␤ 2 adrenoreceptor and EP prostanoid receptors. Interleukin-1␤ significantly increased isoprenaline-induced cAMP accumulation by increasing ␤ 2 adrenoreceptor numbers via a protein kinase A-dependent mechanism. In contrast, interleukin-1␤ significantly impaired prostaglandin E 2 -induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
14
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 36 publications
(27 reference statements)
4
14
1
1
Order By: Relevance
“…Joy and Cowley, in contrast, reported that Calu-3 cells express all four known EP-R subtypes, but point to EP4-Rs in the regulation of CFTR-dependent iodide efflux (28). Via RT-PCR, we only detected EP4-Rs in our Calu-3 cells, and EP4 inhibition was sufficient to prevent CFTR activation, confirming the results of Clayton and colleagues (29).…”
Section: Discussionsupporting
confidence: 79%
“…Joy and Cowley, in contrast, reported that Calu-3 cells express all four known EP-R subtypes, but point to EP4-Rs in the regulation of CFTR-dependent iodide efflux (28). Via RT-PCR, we only detected EP4-Rs in our Calu-3 cells, and EP4 inhibition was sufficient to prevent CFTR activation, confirming the results of Clayton and colleagues (29).…”
Section: Discussionsupporting
confidence: 79%
“…These results contrast with those published in Calu-3 cells, where p38 MAP kinase pathways were involved in IL-1␤-stimulated CFTR-dependent Cl Ϫ currents (14). These results also contrast with previous measurements in Calu-3 cells showing that IL-1␤ affected cAMP and Cl Ϫ permeability differentially when added together with either prostaglandin E2 or isoproterenol (6). The contradictions may result from differences in the transport machinery expressed in Calu-3 compared with the native tissue.…”
Section: Discussioncontrasting
confidence: 57%
“…Eicosanoids with well-described prominent airway/pulmonary effects (related primarily to asthma and airway function) include TXA2, PGD2, PGE2, and PGI2, and many of the accompanying receptors have been described to signal through G s and cAMP. Recent studies suggest that EP2 and EP4 are expressed in Calu-3 cells, where they can activate CFTR, and an inverse regulatory relationship between IL-1␤ and PGE2 has recently been described in airway epithelia (42,43). PGE2, PGF2␣, and to a lesser extent 15-HETE have also been detected on the apical surface of porcine airway cell monolayers, which was augmented after stimulation with calcium-mobilizing agents and AA (44).…”
Section: Discussionmentioning
confidence: 96%